Walking like a toddler: Students' autonomy development in English during cross-border transitions. (July 2016) - Ding, Feng; Stapleton, Paul
Abstract: The language-related challenges affecting international university students' adaptation to a new host environment have been extensively explored in English-speaking countries. However, few studies have been performed in non English-speaking countries or regions, and even fewer have investigated these challenges from the perspective of learner autonomy. Adopting a process-oriented approach, the present qualitative, multiple case study examines how nine first-year mainland Chinese university students developed their autonomy in adapting to English-medium-instruction (EMI) in a university in Hong Kong, a multilingual context. The findings reveal that, via a three-stage process, the participants developed autonomy by changing their strategies for both learning and using English during their first year of study. The participants' development of autonomy for learning and using English was also mediated by the local multilingual context. These findings help to deepen our understanding of the dynamics and complexity of students' long-term autonomy development in an era of increasing internationalization in higher education.